INTERDISCIPLINARY JUDICIAL COOPERATION: MUTUAL RECOGNITION OF PROTECTION MEASURES IN EUROPEAN UNION - Anca Magda VOICULESCU (Challenges of the Knowledge Society)
Violence under multiple forms has become an increasingly worrying phenomenon in current society, leading to adoption of various legislative instruments, in order to effectively combat it. According to particularities of each state, there is a wide variety of instruments adopted at national level, different either in name (interdiction orders, protection orders, restrictive orders, etc.), as well as juridical nature (civil or criminal). The same variety also appears at EU level, related to the type of legislation (mandatory or not; primary or secondary) and the area it covers (civil or criminal). The panel of legislative instruments is completed by a series of international conventions on preventing and combating violence. In this large context, the purpose of the article is to analyze interdisciplinary issues related to judicial cooperation within European Union in civil and criminal matters, for the particular case of protection measures adopted by different authorities of Member States. The principle is that exercise of the right of free circulation and establishment in European Union imposes that protection granted to an individual in a Member State should be maintained and continued in any other Member State to which that person travels or moves. In particular, this goal is achieved by recognition in a Member State of the effects of judgments providing protection measures handed down in another Member State. The objectives of this study are to identify the relevant compulsory EU legal instruments in the field of civil and criminal areas, as well as a comparative perspective concerning the relation between previously identified EU law and national legislations and their sphere of application. Equally, the comparative approach will extend to establishing the main issues specific to exequatur procedure both at EU and national level.